A feasibility study of avoiding positive calcium balance and parathyroid hormone increase in patients on peritoneal dialysis - Maria Clara Teixeira Piraciaba; Lilian Cordeiro; Erica Adelina Guimarães; Hugo Abensur; Benedito Jorge Pereira; Vanda Jorgetti; Rosa Maria Affonso Moysés; Rosilene Motta Elias (Bone Reports, 2022)
Background: The effect of the dialysate calcium concentration (D[Ca]) on mineral and bone metabolism in patients on peritoneal dialysis (PD) is overlooked. D[Ca] of 1.75 mmol/L is still prescribed to many patients on PD around the world. Previous studies on the effects of reducing D[Ca] have been carried out before the incorporation of calcimimetics in clinical practice. We hypothesized that a reduction in D[Ca] is safe and without the risk of a rise in serum parathyroid hormone (PTH). Methods: In this non-randomized clinical trial, the D[Ca] was reduced from 1.75 mmol/L to 1.25 mmol/L for one year in prevalent patients on PD. Demographic, clinical, and CKD-MBD-related biomarkers were evaluated at baseline, 3, 6, and 12 months of follow-up. Results: 20 patients completed 1-year follow-up (56 ± 16 years, 50 % male, 25 % diabetic, 55 % with baseline parathyroid hormone – PTH >300 pg/mL). Over time, there was no significant change in calcium, phosphate, total alkaline phosphatase, 25(OH)-vitamin D or PTH, although adjustments in calcitriol and sevelamer prescription were required. After 1 year, absolute and percentual change in PTH levels were 36 (−58, 139) pg/mL, and 20 % (−28, 45) respectively. The proportion of patients with PTH > 300 pg/mL did not change during the follow-up (p = 0.173). Conclusion: Knowing the risk of a positive calcium balance in patients on PD, reducing the D[Ca] concentration is a safe and valuable option, although medication adjustments are needed to detain PTH rising.